ANALISIS MANAJEMAN MODAL KERJA DALAM MENINGKATKAN PROFITABILITAS PADA PT. PEGADAIAN(PERSERO) KANTOR WILAYAH II PEKANBARU - Devi Herlina Margareta; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Cooperative is a business entity established to support the people's economic movement which has duties and responsibilities aimed at the welfare of members and the general public. The purpose of this study was to assess the financial performance of KSU Rejosari District of Tenayan Raya Pekanbaru City by using financial ratios. The location of this research was conducted at the KSU Rejosari’s District of Tenayan Raya Pekanbaru City. Ratio analysis used is the profitability that is current ratio, the solvency ratio that is debt to asset ratio (DAR) and debt to equity ratio (DER), the ratio of activity that receivable turnover, and the profitability ratio that is net profit margin (NPM) and return on assets (ROA) and return on equity (ROE). The analytical method used is quantitative descriptive.Research conducted based on the standards of the Regulation of the Minister of Cooperatives and Small and Medium Enterprise of the Republic of Indonesia Number: 06/Per/M.KUKM/V/2006 concerning Cooperative Guidelines Achievers. Based on the calculation of liquidity ratios seen from the level current ratio of KSU Rejosari's performance is categorized as not good. The results of the calculation of the solvency ratio seen from the DAR and DER of KSU Rejosari's performance are categorized as good. The results of the calculation of the activity ratio seen from the level receivable turnover of KSU Rejosari's performance are categorized as not good. The results of the calculation of profitability ratios seen from the level of NPM and ROA performance are categorized very good, while the level of ROE performance of KSU Rejosari is categorized as good. Keywords: Financial Performance, Liquidity Ratio, Solvency Ratio, Activity Ratio, Profitability Ratio